Acceleration of Spatial Correlation Based Hardware Trojan Detection Using Shared Grids Ratio - Esirci, Fatma Nur; Bayrakçı, Alp Arslan (Springer, 2020)
Due to mostly economic reasons almost all countries including the developed ones have to handle integrated circuit designs to a foreign fab for manufacturing, which raises the security issues like intentional malicious circuit (hardware Trojan) insertion by an adversary. A previously proposed method to address these security issues detects hardware Trojan using the spatial correlations in accordance with delay based side channel analysis. However, it is never applied to full circuits and it requires too many path delay computations to select correlated path pairs. In this paper, we first apply the method and present the results for full circuits and then, the method is accelerated by proposing a novel path selection criterion which avoids the computation of path delays. In terms of detection success, the resultant method performs similar to the previous one, but in a much faster fashion. © 2020 Elsevier B.V., All rights reserved.
8th International Conference on Mathematical Aspects of Computer and Information Sciences, MACIS 2019 -- Gebze -- 238969
Keywords: Hardware security; Hardware Trojan; Process variations; Side channel analysis; Spatial correlations